Diagnosis dan Tatalaksana Sindrom Wernicke-Korsakoff - Agustiawan Agustiawan; Feby Purnama (Majalah Kedokteran Indonesia, 2024)
Wernicke-Korsakoff syndrome is a common complication of thiamine (vitamin B1) deficiency. The prevalence of Wernicke-Korsakoff syndrome (WKS) worldwide is 0-2%, especially in the homeless, elderly, and psychiatric patients. Individuals with malnutrition due to any cause are at risk for developing WKS. The most common social factor associated with WKS is chronic alcohol abuse. Ethanol has been shown to interfere with thiamine absorption in the gastrointestinal tract. The syndrome is classically described as a clinical triad consisting of altered mental status (confusion or dementia), nystagmus (or ophthalmoplegia), and ataxia. The diagnosis of WKS is based on the history and clinical findings supplemented by laboratory and radiological examinations. Treatment of thiamine deficiency in patients suspected of having Wernicke’s is intravenous injection of thiamine 500 mg infused over 30 minutes. The drug is given three times daily for two days. Thereafter, transition to 250 mg either intravenously or intramuscularly once daily for 5 days.